Women entrepreneurs and their bank selection criteria: An exploratory study - Mahmood, Rosli (Institut Bank-Bank Malaysia, 2005)
This paper focuses on a study that examined bank selection criteria employed by women entrepreneurs in Malaysia.A total of 100 women business owners participated in the study.The findings reveal that the main factors determining bank selection are: fast and efficient service, ease of obtaining loans, reception received at the bank, friendliness of bank personnel, lower interest charges on loans, bank's reputation and image, confidence in bank manager and confidentiality of bank. The findings are of interest to bankers because they provide information on the selection criteria by a crucial segment of potential customers.